A Case of Melioidosis Probably Acquired by Inhalation of Dusts During a Helicopter Flight in a Healthy Traveler Returning From Singapore. Issue 1 (2nd September 2014) - Amadasi, Silvia; Dal Zoppo, Sarah; Bonomini, Annalisa; Bussi, Anna; Pedroni, Palmino; Balestrieri, Gianpaolo; Signorini, Liana; Castelli, Francesco
Abstract : We present a case of melioidosis in an Italian male returning from Singapore after a short travel. He probably acquired the disease by inhalation, which is not the typical mode of transmission, in the absence of evident risk factors. The diagnosis was confirmed by real‐time polymerase chain reaction of the culture while serology was useful to assess professional exposure among laboratory workers. Treatment consisted of an initial intensive phase with meropenem and trimethoprim–sulfamethaxazole (TMP–SMX), followed by 6 months of eradication therapy with TMP–SMX.